(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2017)
Fractionation and purification of stem bark extract of Bridelia stipularis growing in Bangladesh afforded glut-5(6)-en-3-one (1), glut-5(6)-en-3?-ol (2), and (22E)-7-hydroxy-28-methylcholesta-4,22-dien-3-one (3). Compound 3 appears to be new, while compounds 1 and 2 have never been reported from this plant. The isolated compounds isolated exhibited cytotoxic activity against brine shrimp nauplii having significant LC50 and LC90 and moderate to strong antimicrobial activity against 13 Gram positive and Gram negative bacterial strains and 3 fungi. Here, compound 1 demonstrated highest inhibition of growth of microorganisms with zone of inhibition of 22.7 mm against Escherichia coli and compound 2 displayed zone of inhibition of 20.8 mm against Candida albicans. Compounds 1-2 also revealed moderate free radical scavenging activity in the DPPH method. Dhaka Univ. J. Pharm. Sci. 15(2): 221-225, 2016 (December)